Mercator the man who mapped the planet - Crane, Nicholas (Weidenfeld & Nicholson, 2002)
A biography of Gerard Mercator, the sixteenth-century mapmaker who created the first two-dimensional projection of the globe.
Keywords: Mercator, Gerhard <1512-1594>; Mercator, Gerhard -- 1512-1594; Geschichte 1500-1600; Geschichte 1537-1606; Cartografie; Geschichte; Cartographers -- Biography; Cartography -- History -- 16th century; Kartografie; Biografie